Perancangan Sistem Informasi Geografis Lokasi Objek Wisata Di Kota Lubuklinggau Berbasis Android - Karman, Joni; Mulyono, Hardi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The Problem In Finding and acces a tourism location in Lubuklinggau, be a primary problem, Especially for tourism or visitoe or tourism from other place in Indonesia. We know that the technology more being advance, but this case make we to improve our potency in Lubuklinggau. Hopely this application which will be made, will appliance the web technology service, in order to the information about tourism will be up to date and to solve this problem the researcher use digital map model approach or SIG based on Android by using Google Maps as the map digital. The method which used in tihs research is UML (Unifide Modelling Language), PHP Program, Java and database Mysql as the data saving geografic information system (GIS) tourism has two programs they are, administration programe for processing tourism data base on web and programe for the user, we use Android aplication. Geografic information system has a goal to give an easy and faster information about tourism in Lubuklinggau